2019
DOI: 10.1111/nph.15662
|View full text |Cite
|
Sign up to set email alerts
|

Multilab EcoFAB study shows highly reproducible physiology and depletion of soil metabolites by a model grass

Abstract: Summary There is a dynamic reciprocity between plants and their environment: soil physiochemical properties influence plant morphology and metabolism, and root morphology and exudates shape the environment surrounding roots. Here, we investigate the reproducibility of plant trait changes in response to three growth environments. We utilized fabricated ecosystem (Eco FAB ) devices to grow the model grass Brachypodium distac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 60 publications
0
79
0
Order By: Relevance
“…The use of inert substrates such as glass beads or sand instead of soil or clay that strongly absorbs a variety of metabolites may affect exudation and metabolite profiles. Notably, root exudation studies of Brachyodium grown under sterile hydroponic systems resulted in similar metabolite profiles of exudates in sand or glass beads ( Kawasaki et al, 2016 ; Sasse et al, 2019 ). The most common organic acids released from Brachypodium roots were malate, citrate, succinic, fumarate, and oxalate ( Kawasaki et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of inert substrates such as glass beads or sand instead of soil or clay that strongly absorbs a variety of metabolites may affect exudation and metabolite profiles. Notably, root exudation studies of Brachyodium grown under sterile hydroponic systems resulted in similar metabolite profiles of exudates in sand or glass beads ( Kawasaki et al, 2016 ; Sasse et al, 2019 ). The most common organic acids released from Brachypodium roots were malate, citrate, succinic, fumarate, and oxalate ( Kawasaki et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…EcoFABs are 3D printed, scalable, and axenic, allowing multiple soil factors to be tested individually and in combination. Right: the EcoFABs showed that root hair development is influenced by filtered soil extracts differently to P supply [109]. Abbreviations: E, root epidermis; n, nucleus; rh, roothair.…”
Section: Where To Next: Fields Of Discovery In the Rhizosphere That Imentioning
confidence: 99%
“…But how can the large number of variables in the rhizosphere be systematically combined for the understanding of processes? An exciting multi-lab approach has been initiated, using repeatable, 3D printed microcosms called Eco-Fabs ( Figure 5C) [109]. Bespoke phenotyping platforms are available globally in fixed locations with highly specialized operators for researchers, breeders, and prebreeders [46].…”
Section: Where To Next: Fields Of Discovery In the Rhizosphere That Imentioning
confidence: 99%
“…As 3D printer technology becomes more affordable and accessible worldwide, there is an opportunity to use this to facilitate research coordination and scientific reproducibility. The EcoFAB project has shown great promise at coordinating research across multiple groups with each printing the same 3D printable growth system and following defined protocols with reproducible results [ 2 , 10 ]. A hurdle for reproducibility of lab protocols is having accessibility to the respective lab equipment.…”
Section: Future Perspectivesmentioning
confidence: 99%